The Role of Calcaneofibular Ligament Injury in Ankle Instability: Implications for Surgical Management. Issue 2 (February 2019) - Hunt, Kenneth J.; Pereira, Helder; Kelley, Judas; Anderson, Nicholas; Fuld, Richard; Baldini, Todd; Kumparatana, Pam; D'Hooghe, Pieter
Background: Acute inversion ankle sprains are among the most common musculoskeletal injuries. Higher grade sprains, including anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL) injury, can be particularly challenging. The precise effect of CFL injury on ankle instability is unclear. Hypothesis: CFL injury will result in decreased stiffness, decreased peak torque, and increased talar and calcaneal motion and will alter ankle contact mechanics when compared with the uninjured ankle and the ATFL-only injured ankle in a cadaveric model. Study Design: Descriptive laboratory study. Methods: Ten matched pairs of cadaver specimens with a pressure sensor in the ankle joint and motion trackers on the fibula, talus, and calcaneus were mounted on a material testing system with 20° of ankle plantarflexion and 15° of internal rotation. Intact specimens were axially loaded to body weight and then underwent inversion along the anatomic axis of the ankle from 0° to 20°. The ATFL and CFL were sequentially sectioned and underwent inversion testing for each condition. Linear mixed models were used to determine significance for stiffness, peak torque, peak pressure, contact area, and inversion angles of the talus and calcaneus relative to the fibula across the 3 conditions. Results: Stiffness and peak torque did not significantly decrease after sectioning of the ATFL but decreased significantly after sectioning of the CFL. Peak pressures in the tibiotalar joint decreased and mean contact area increased significantly after CFL release. Significantly more inversion of the talus and calcaneus as well as calcaneal medial displacement was seen with weightbearing inversion after sectioning of the CFL. Conclusion: The CFL contributes considerably to lateral ankle instability. Higher grade sprains that include CFL injury result in significant decreases in rotation stiffness and peak torque, substantial alteration of contact mechanics at the ankle joint, increased inversion of the talus and calcaneus, and increased medial displacement of the calcaneus. Clinical Relevance: Repair of an injured CFL should be considered during lateral ligament reconstruction, and there may be a role for early repair in high-grade injuries to avoid intermediate and long-term consequences of a loose or incompetent CFL.